Teachers’ Perceptions of Technology Integration in Teaching-Learning Practices: A Systematic Review - Akram, Huma; Abdelrady, Abbas Hussein; Al-Adwan, Ahmad Samed; Ramzan, Muhammad (Frontiers in Psychology, 2022)
The rapid expansion of the Information and Communication Technologies (ICTs) has transformed learners into digital learners, requiring teachers to integrate technology into their pedagogical approaches, where teachers’ attitudes, technological knowledge, and skills play a significant role in its effective integration. From this perspective, the current study presents teachers' perceptions regarding technology integration in their teaching-learning practices at all educational levels in light of the previous studies performed in the last five years in Pakistan. The findings reveal that teachers exhibit a positive perception regarding technology integration in teaching-learning practices. They believe that technology-incorporated teaching assists them in enhancing their instructional practices effectively, making the learning process exciting and interactive, and keeping learners motivated. Regarding barriers, the slow speed of the internet, load shedding, lack of infrastructure, online teaching experience, and training were reported as the main obstacles that hinder teachers from effective integration of ICT into their teaching practices. And institutional support Accordingly, the study findings suggest that concerned authorities should set clear and effective policies to make efficient use of ICT by allocating a sufficient budget and ensuring all necessary facilitation (e.g., ICT infrastructure, tools, software, internet, and labs) in all educational institutions. Furthermore, particular attention should be devoted to supplying adequate opportunities for the career development of teachers in developing technological competencies, which help them successfully use ICT in their instructional practices.